2004
DOI: 10.1002/icd.366
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of middle childhood psychosomatic problems: An emotion regulation approach

Abstract: Development of the psychosomatic problems picky eating and headache and stomachache complaints in middle childhood was investigated from an emotion regulation perspective. The role of negative emotionality and family emotion regulatory factors (attachment to mother and parental perceived control) was studied. The sample ðN ¼ 87Þ was a predominantly middleclass, community sample. The study was longitudinal, based on data from several data collections between child age 11 months and 9 years. The results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…This pattern suggests that when confronted with a difficult situation with their best friend, insecure boys may have difficulty regulating the appropriate emotion. Existing literature does suggest that there is a negative association between attachment security and emotion regulation (Hagekull & Bohlin, 2004) and that the role of emotion regulation in SIP is important (Lemerise & Arsenio, 2000). Here, we have shown that the ability to choose an adaptive emotion may be difficult for boys who have an insecure relationship with their fathers.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern suggests that when confronted with a difficult situation with their best friend, insecure boys may have difficulty regulating the appropriate emotion. Existing literature does suggest that there is a negative association between attachment security and emotion regulation (Hagekull & Bohlin, 2004) and that the role of emotion regulation in SIP is important (Lemerise & Arsenio, 2000). Here, we have shown that the ability to choose an adaptive emotion may be difficult for boys who have an insecure relationship with their fathers.…”
Section: Discussionmentioning
confidence: 99%
“…The intercorrelation between the two scales was r = -0.56, p \ 0.001. Before summing scores from the two scales to form one measure of emotion regulation, inhibitory control scores were reversed and both scales were standardized [17,37]. A high value denoted that the child was high in anger/frustration and low in inhibitory control (hereinafter referred to as maladaptive emotion regulation).…”
Section: Emotion Regulationmentioning
confidence: 99%
“…This is important for prevention, treatment and recovery from the disease. Conclusions HPR, a part of negative emotionality, already proved to be related to psychosomatic disorders [9] of temperament, is an important risk factor for developing migraine, but not other primary headaches.…”
Section: )mentioning
confidence: 87%